Obtenção da sequência mitocondrial e desenvolvimento de marcadores moleculares do tipo microssatélites para duas espécies de serpentes: Boa constrictor constrictor e Epicrates crassus - Nazaré Lúcio de Abreu (2022)
Popularly known as savannah python (Epicrates crassus) and python (Boa constrictor constrictor) are two species widely marketed as pets throughout Brazil due to their beauty and for being docile and easy to handle. This work aimed to develop molecular markers based on microsatellite regions and the sequencing of the mitochondrial genome of the two species to assist criminal authorities in the identification of these species and thus apply the penalties applicable to those who trade these animals illegally. The sequencing of both genomic and mitochondrial DNA was performed using Next Generation Sequencing (NGS) technology. After assembling the contigs using Geneious, searches for microsatellite regions were performed using the SciRoKo software. The company did Integrated DNA Technologies the design of the 53 pairs of primers in Geneious followed by the syntheses. After the calibration tests, 15 pairs of primers were selected for each of the species that can be used in later tests with individuals of the same species and of different species. The publication of the mitochondrial genome will also allow other researchers to study these species or others of the same genus with the design of mitochondrial markers.